Intracellular chloride concentration changes modulate IL-1β expression and secretion in human bronchial epithelial cultured cells - Clauzure, Mariángeles (2017)
Fil: Clauzure, Mariángeles. Pontificia Universidad Católica Argentina. Facultad de Ciencias Médicas. Instituto de Investigaciones Biomédicas. Laboratorio de Biología Celular y Molecular; Argentina